Unconventional monetary policy and risk-taking: Evidence from agency mortgage REITs - W. Scott Frame; Eva Steiner (Federal Reserve Bank of Atlanta, 2018)
We study how the Federal Reserve's quantitative easing (QE) influenced the behavior of Agency mortgage real estate investment trusts (REITs) - a set of institutions identified by the Financial Stability Oversight Council as posing systemic risk. We document that Agency mortgage REITs: [i] equity prices reacted to QE announcements and in a manner consistent with their business prospects; [ii] grew markedly during QE2 and receded during QE3 in relation to the Federal Reserve's Agency MBS purchase activity; and [iii] increased their leverage during QE3. Our findings are consistent with unconventional monetary policy actions crowding out private investment and "reaching for yield" behavior by financial institutions.
Keywords: E58; G21; G23; G28; 330; quantitative easing; risk-taking; REITs; GSEs; mortgages; securitization